Karakteristik Kimia Lahan Gambut Dangkal dan Potensinya untuk Pertanaman Cabai dan Tomat - Muhammad Alwi; Anna Hairani (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2007)
Experiment was conducted on shallow peat with depth (50 - 75 cm) and C/D flooding type at Purwodadi village, Maliku District, Pulang Pisau Regency, Central Kalimantan in wet season 2003.  Ten samples were taken from areal of 2 ha for studying characteristics of shallow peat.  Nutrient absorption of crops and soil nutrient after harvesting  were also analyzed.  This experiment used split plot design with three replications.  As a main plot was input application (M1) : manure (5.000 kg/ha), lime (2.000 kg/ha), urea (150 kg/ha), SP36 (312.5 kg/ha) and KCl (200 kg/ha) for tomato and SP36 (187.5 kg/ha) and KCl (125 kg/ha) for red pepper and without application (M0). Five varities of red pepper (Tombak 1, Tanjung 1, Tanjung 2, Prabu and Hot Chilli) and, five varities of tomato (Oval, Ratna, Mirah, Berlian and Permata) were as subplots. The results showed that soil chemical characteristics were : peat depth 50 - 75 cm, phyrite depth 75 - 100 cm, soil pH 3.5 - 4.0, C-organic content 12 - 24 %; range of nutrient availability : N (0.4 - 0.6 %), P (30 - 50 ppm P), K (0.1 - 0.3 me/100 g), Ca (1 - 6 me/100 g), Mg (0 - 1 me/100 g), Fe (20 - 120 ppm Fe) and Al (1 - 7 me/100 g).  Availability of nutrients N, P, K, Ca, and Mg was low, and it could be increased by application of some inputs such as manure, lime, urea, SP36 and KCl.  Low nutrient availability and crop absorption especially K, Ca, and Mg was a main factor that retarded crop growth.  Red  pepper and tomato yields ranged 0.59 - 4.02 and 4.77 - 10.99 t/ha for control treatments and 3.44 - 7.72 and 14.85 - 35.98 t/ha with input application.   Key words : amelioration, yield potency, red pepper, tomato, shallow peat